Experimental Study of Maximum Stresses in the Stationary Hoist Design in the Ansys Software Environment - Donenbaykyzy Kassymzhanova, Aidana; Kenesovich Ibatov, Marat; Temirgalievich Balabayev, Oyum; Serikovich Donenbaev, Bakytzhan; Ikhtiyarovich Ilessaliyev, Daurenbek (Communications - Scientific Letters of the University of Zilina, 2022)
The authors have studied the methods of loading bulk cargo in the railway transport. The developed method of loading bulk cargoes into containers transported by railway platforms has been developed. The article deals with experimental studies of maximum stresses in the design of the proposed stationary hoist. The studies have been carried out in the ANSYS software environment with development of simulation models of the hoist design.
Keywords: railway transport; railway platform; container; bulk cargo loading; stationary hoist; simulation modeling; export